A Multi-instrument Study of Microwear Polishes on Mousterian Tools from Weasel Cave (Myshtulagty Lagat), Russia. (3rd July 2017) - Kimball, Larry R.; Coffey, Tonya S.; Faulks, Nathan R.; Dellinger, Stephen E.; Karas, N. Matt; Hidjrati, Nazim
ABSTRACT: The functions of flaked stone tools are usually determined by the observation of microwear polishes with the incident-light microscope with magnifications of 50–400× – known as the Keeley Method. In our study into the function of Mousterian flint tools from Weasel Cave, we employ the atomic force microscope (AFM) and the optical interferometer, in addition to the light microscope and the SEM. The advantage of the AFM and the interferometer are the extremely high resolution permitted and most importantly the quantitative data extracted from microwear polishes. The merits of these different instruments are discussed in the context of polish differentiation for microwear traces on archaeological specimens interpreted as due to contact with meat, fresh hide, dry hide, bone, wood, as well as hafting. A multi-instrument approach contributes to the understanding of the formation of microwear polishes as well.